Graphene-Based Materials for Biotechnological and Biomedical Applications: Drug Delivery, Bioimaging and Biosensing - Singh, D (Elsevier Ltd, 2023)
Graphene is a highly versatile two-dimensional carbon-based material employed in several research areas having progressive characteristics comprising properties like high surface area, transport, thermal, optical, elasticity, strength etc. Graphene-based composite materials are considered to be potentially smart candidates for various biomedical application areas and are frequently used in medical applications and apply in electronics, implants, devices, and other biomedical-related applications. Compared to graphene, its derivatives, graphene oxide and reduced graphene oxide, easily exfoliated from chemically oxidized graphite, are favourable materials for biomedical applications due to their outstanding surface functionalizability, aqueous processability, amphiphilicity, fluorescence quenching, etc. In this proposed review article, we have selectively assessed the latest research to apply graphene and its derivatives with polymer/nanoparticles in biomedical applications like drug/gene delivery, tissue engineering, bioimaging, biosensing, and magnetic resonance imaging. The exposure of graphene materials in biotechnological/biomedical applications has also led to a summary of their effects on human health and the environment. This review article is expected to provide helpful existing knowledge and inspire new ideas to enhance secure and effective biotechnological/biomedical devices based on graphene materials. © 2023 Elsevier Ltd